DAMPAK DIGITALISASI DAN INOVASI DALAM ORIENTASI KEWIRAUSAHAAN PEREMPUAN TERHADAP NIAT MEMULAI USAHA YANG BERKELANJUTAN - Maihani, Syarifah; Shafira, Syarifah Nayla; Firly, Windianet; Saddiyah (Faculty of Economics and Business, Universitas Malikussaleh, 2024)
Digitalization and innovation have become important factors in changing the entrepreneurial landscape, especially for women who want to start a business. This study aims to analyze the influence of digitalization and innovation on women's entrepreneurial orientation and its impact on sustainable business start-up intentions. Through a quantitative approach with survey method, the study involved a number of women entrepreneurs who are active in various sectors. The research instrument used a structured questionnaire to measure the variables of digitalization, innovation, entrepreneurial orientation, and sustainable entrepreneurial intention. Data analysis was conducted using inferential statistical techniques, such as linear regression and path analysis, to test the relationship between variables. A total of 100 Aceh Bireuen women entrepreneurs were carefully sampled. The findings of this study have practical implications for policy makers, business support entrepreneurs, and aspiring women entrepreneurs in Aceh Bireuen. Aceh Bireuen can inform the design and implementation of targeted interventions and support mechanisms that promote entrepreneurship and innovation in sustainable development. This article illustrates and explains how dynamic capabilities moderate the relationship between women's entrepreneurial orientation and sustainable business start-up intentions and how digitalization moderates the relationship between innovation and business start-up intentions in the context of Aceh Bireuen.